Impulse technology for micro coating of titanium nitride at the end of compressor blades - Орланов, В.Й.; Чумак, О.І. (Proceedings of National Aviation University (archive), 2006)
Technology of use of low-temperature plasma for realization of plasma chemical processes of plating of protective cover in application to end face sputtering of compressor blades is considered.